Examining The Impact Yoga Training on The Mental Health Among Armed Reserved Police - S, Thiruvangadam; Mohanakrishnan, R.; V, Natesamurthy; Pranav Prakash, Prabhu; R, Ganesh (Journal of Neonatal Surgery, 2025)
Yoga training has increasingly been recognized as a vital tool for improving mental health. Regular yoga practice helps reduce stress by promoting relaxation through deep breathing and mindfulness techniques. Studies have shown that yoga can lower levels of cortisol, the stress hormone, and improve overall mood by enhancing neurotransmitter function, such as serotonin and dopamine. Police officers face significant mental pressure due to the nature of their work, which often involves high-stakes situations, trauma, and constant vigilance. The demands of protecting public safety, dealing with violent crimes, and responding to emergencies can lead to stress, anxiety, and even post-traumatic stress disorder (PTSD) among officers. Therefore, the goal of this study is to examine how yoga training affects the mental health of police officers in the Armed Reserve. In order to achieve the goal of this study, forty (N=40) men police were selected randomly from Cuddalore District. Their age ranged from 25 to 40 years. Selected subjects underwent 12 weeks of yoga training. The collected data was statistically analyzed to produce the results. Based on the statistical results, it was concluded that yogic intervention significantly improved the mental health of armed reserved police 0.05.